The Adaptation and Validation of Quality of Work Life Scale to Turkish Culture - Afsar, S.; Burcu, E. (Springer Netherlands, 2013)
The aim of this research is to adapt the Quality of Work Life Scale developed by Sirgy et al. (Social Indicators Research, 55, 241–302, 2001) to Turkish culture, and to examine its psychometric properties. The research has been conducted on 254 academics who are affiliated to the Faculty of Education and Faculty of Science and Letters of four different universities in Ankara, Turkey. In order to provide the lingual equivalence, bilingual group pattern was used, and an English version of the scale was applied to a group of 34 academicians who are fluent in both English and Turkish. Nearly 1 month after this application, the Turkish version of the same form was applied once again to the same 34 people. The construct validity of the scale was conducted by using the Confirmatory Factor Analysis method. As a result of the study, it was determined that the original scale and its Turkish form yielded similar results. The fact that internal consistency is high is proved. Croanbach alpha coefficient was found as 0.84. This result indicates that the internal consistency of the test and accordingly the reliability are high and close to the original QWL scale. As a result of the Confirmatory Factor Analysis applied, it was determined that the Turkish form gave a factorial structure which was similar to the original scale and that no problems occurred in the course of using the scale total points. It is concluded that this scale, with its extremely comprehensible language, will contribute to defining the level of quality of the work life of those who work in Turkey and understand their behaviors and attitudes towards their work.